Trends and future of human resource management in the 21st century - M. K. GANESHAN; C. Vethirajan (Universitas Pendidikan Nasional, 2021)
Every business is made up of people, its human resources. An organization is nothing without human resources. Human resource management is about managing these people effectively. Now, more than ever, HRM is recognized as being critical to the survival and success of organizations. Continuous changes in technology, economic, social, and psychological understandings, and structures have an influence on both Human Resources and their management. As firms strive to make the HR department leaner and more strategic, current HRM models show that expectations about HR jobs are evolving. Human resource management is critical to every organization's success. It is a source of support and strength. In the present complex milieu, organizations are greatly influenced by changes taking place in internal as well as external environments, no business or organization can change or exist or grow without appropriate human resources. Therefore, human resources have become the focus of attention of every progressive organization. In the changing world, the philosophy and perspective of HRM need to transform and redesign. This paper attempts to spotlight the latest trends in HRM for the present century like Globalization of Economy, Corporation Restructuring, Newer Organizational Designs, Total Quality Management, Kaizen model, etc.